PENCATATAN AKUNTANSI PADA USAHA PETERNAKAN AYAM PETELUR ( Studi Kasus Usaha Peternakan Ayam Petelur di Kecamatan Sugio Lamongan ) - Andrianto, Andrianto; nuraini, fitri; Maharani, Rieska (Majalah Ekonomi, 2017)
Accounting is an information system that generates a report to the parties concerned of the economic activity and the condition of the company. Micro, Small and Medium Enterprises (SMEs) as the support of the nation's economy is still many who have not applied the accounting in business. This study aims to identify and analyze the application of accounting at the Micro, Small and Medium Enterprises (SMEs) as well as the constraints faced in this dalamnya.Penelitian took 3 SMEs in the field of poultry farm located in Lamongan district by using a sampling method in order to conduct interviews the validity of the information received. The results showed that most, poultry breeders do not neatly financial records. Breeders only record cash received as out, the majority of these transactions take place every day in business management. The problem faced by the farmers is the lack of knowledge and educational background of the farmers, the financial accounting records. Besides, the lack of local government's role in providing training and guidance, especially in the accounting records. Keywords: Accounting, Poultry, SAK-ETAP,UMKM